GAMBARAN KINERJA KEUANGAN PT SEMEN BATURAJA (Persero) Tbk. - Hanin Dalilah Aksara; Choiruddin Choiruddin; Zaliah Zaliah; Sofyan AR (EKSISTANSI, 2021)
The purpose of this research is to analyse how the potential financial difficulties in the cement industry listed on the Indonesia Stock Exchange using Altman model and Springate model aimed at determining the potential of bankruptcy in PT Semen Baturaja (Persero) Tbk. The author uses secondary data is the financial report of 2012-2018 The study results shows that the financial performance of PT Semen Baturaja (Persero) Tbk Period 2012 to 2018 have financial difficulties. Results of financial distress prediction or bankruptcy prediction using Altman model (Z-Score) at PT Semen Baturaja (Persero), Tbk is in grey area or prone to bankruptcy, which is experiencing financial difficulties in 2017 and 2018 while Springate model is distress and have bankruptcy in 2017 and 2018.